The advanced lung cancer inflammation index predicts outcomes of patients with non-small cell lung cancer following video-assisted thoracic surgery. Issue 12 (December 2021) - Han, Zhaohui; Hu, Zhonghui; Zhao, Qingtao; Xue, Wenfei; Duan, Guochen
Objective: The advanced lung cancer inflammation index (ALI) predicts overall survival (OS) in patients with advanced lung cancer. However, few studies have tested ALI's prognostic effect in patients with non-small cell lung cancer (NSCLC) following video-assisted thoracic surgery (VATS), especially patients at stage III. This study investigated the relationship between ALI and outcomes of patients with NSCLC following VATS. Methods: We retrospectively examined 339 patients with NSCLC who underwent VATS at Hebei General Hospital, China. Preoperative clinical and laboratory parameters were collected and analyzed. Optimal cutoff values of potential prognostic factors, including ALI, were determined. Kaplan–Meier and Cox regression analyses were used to determine each factor's prognostic value. Results: The median OS was 31 months. The optimal cutoff value for ALI was 41.20. Patients with high ALI (≥41.20) displayed increased OS (33.87 vs. 30.24 months), higher survival rates, and milder clinical characteristics. Univariate and multivariate analyses showed a significant correlation between ALI and the prognosis of patients with NSCLC, including those at stage IIIA, who underwent VATS. Conclusions: Low ALI correlated with poor outcomes in patients with NSCLC following VATS. Preoperative ALI might be a potential prognostic biomarker for patients with NSCLC following VATS, including patients at stage IIIA.